CHANGE OF MARCHANTIA SP SIZE AND COLOUR RELATED TO DISTANCE FROM WATER RESOURCE IN CUGHUP EMBUN, SOUTH SUMATERA - Marisa, Hanifa (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
An invesgation about size and colour of Marchantia sp moss, had been done in Cughup Embun water fall, Pagar Alam, South Sumatera, Indonesia at November 9th, 2014(end of drough season). The aim was to know wether the distance from water fall (air and soil moisture) should effect the size and colour of those moss. Twenty meters sistematically distance in 4 points locationÂ from above slope to water fall pond; 5, 25, 45, 65 and 85 m were considered for Marchantia sp sampling. Body size, colour and existing of Sporangium were noted. It is found that the size of moss body gradually bigger from 0.8, 1.0, 1.2, 1.3Â and 1.3 cm. Colour of moss change An from pale brown, pale green, green and deep green. AmountÂ of archegoniopore seems exist in many number at 45 m distance from above ground.Keywords: Marchantia sp, moisture, archegoniopore, antheridiopore.